AGRICULTURAL EXTENSION SERVICES AND FARM INPUT SUPPLY LINKAGE IN OGUN STATE, NIGERIA - Adefunke Fadilat Olawunmi AYINDE; Olaoluwa Ayodeji ADEBAYO; Mathias Ofonedu UMUNNA; Azeez Olalekan IBRAHIM (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
This study was carried out to examine the agricultural extension services and farm input supply linkage in Ogun State, Nigeria. Data was obtained from interviewing sixty farmers randomly in Ifo Local Government Area, Ogun State. All the extension agents for the two block offices in the locality were also interviewed to corroborate the data obtained from farmers. Socio-economic characteristics of the respondents were ascertained to have positive influence on agricultural production. Inputs were found out to be supplied mainly by Ogun State Agro-Services Corporation (OGASC) and Ogun State Agricultural Development Programme (OGADEP), but these inputs are not always available at the required time and quantity while the linkage between OGADEP and OGASC was confirmed to be inexistence i.e. OGASC being the commercial arm of OGADEP supplies inputs directly to farmers through the Farm Service Centres (FSCs) and Input Sales Centre at the OGADEP Headquarters. Through these Centres, the farm inputs get to the Block Offices via the Zonal Office, from where the farmers are expected to purchase them. On the other hand, OGADEP supplies information on input needs of farmers to OGASC which assists the latter in making inputs available at the right time and in the right quantity. In addition to this, OGADEP also supply information on input availability to the farmers through the Village Extension Agents (VEAs) who also take recommended practices to these farmers. However, apart from their above mentioned roles, the VEAs are also involved in actual purchase of inputs to the farmers. This deviation from the “professionalism” dictate of the Training and Visit System of Extension Services would have good influence in boosting agricultural production in the study area.